Experimental study of Undershot Type Water Wheels as Picohydro Power Generators in Irrigation Channels (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Riau, 2023)
The need for electrical in rural areas are continues to increase. Meanwhile, the procurement of power plants are limited and experiences many obstacles. The aim of this testing study a hydroelectric power plant in a tourism area is to provide the electricity appropriate that location by utilizing the potential of natural resources. The undershot type water wheel is used as a driving force to drive the electric generator. The resources used come from the flow of irrigation canal which is usually used to irrigate rice fields and the others needs of farmer communities. Measurements of rotation speed, electrical voltage and power produced were carried out within seven days. It is estimated that the generator can produce 75 Watts. The electricity can be utilized for lighting the entrance of tourism areas, food stalls and a residence house. To increase power production found modifications to the irrigation canals need to be considered.